LANSKAP KOLONIAL KOTA BAUBAU SEBUAH PUSAKA PENINGGALAN MASA KOLONIAL DI SULAWESI TENGGARA - Syahadat, Ray March; Arifin, Nurhayati H.S.; Arifin, Hadi Susilo (Paramita: Historical Studies Journal, 2015)
Baubau is appointed as one of heritage cities in Indonesia because it has many historical inheritances. Although Baubau becomes an autonomous region in 2001, some historical records show that  the city has been existed long time ago and passed some phases. One of those phases is the development era by the Dutch Indies Government.  There are many inheritances from colonial period in the city even it is called as the largest in the Province of Southeast Sulawesi. Unfortunately, there are not many research and inventory by related stakeholders toward the colonial heritages in the city. This research aims to record or to list of current assets and to analyze the landscape characteristics of colonial heritages  located in Baubau. The result shows that there are four historical landscapes which save the colonial heritage objects namely the colonial ladscape and early independence day (51 objects), Palabusa (4 objects), Wakonti (1 object), and Chinatown (5 objects). The character  which constructs of the three landscapes generally consist of buildings, structures, and monuments with art deco style. Baubau ditetapkan menjadi salah satu kota pusaka Indonesia karena menyimpan banyak peninggalan sejarah. Meskipun Baubau menjadi daerah otonom pada tahun 2001 tetapi berbagai catatan sejarah menunjukkan bahwa kota ini telah ada sejak zaman dulu dan telah melalui beberapa fase. Salah satunya ialah masa pembangunan oleh pemerintah Hindia Belanda. Banyak peninggalan zaman kolonial di kota ini bahkan bisa dikatakan yang terbanyak se-Provinsi Sulawesi Tenggara. Sayangnya belum banyak penelitian maupun inventarisasi dari stakeholders terkait terhadap peninggalan kolonial di kota ini. Penelitian ini bertujuan menginventarisasi serta menganalisis karakter lanskap  peninggalan masa kolonial yang berada di Kota Baubau. Hasil yang diperoleh, terdapat empat lanskap sejarah yang menyimpan objek-objek peninggalan zaman kolonial yaitu lanskap kolonial dan awal kemerdekaan (51 objek), Palabusa (4 objek), Wakonti (1 objek), dan pecinan (5 objek). Karakter yang menyusun ketiga lanskap tersebut umumnya berupa bangunan, struktur, dan monumen bergaya art deco.